2011
DOI: 10.3390/molecules16119234
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II Enhances Nrf2 Nuclear Translocation to Upregulate Phase II Detoxifying Enzyme Expression Coupled with the ERK, Akt and JNK Signaling Pathways

Abstract: In the present study, the potent inducers of phase II detoxifying and antioxidant stress responsive to icariside II was investigated. First, a dose of 0–10 µM icariside II showed no significantly cytotoxicity on HepG2 cells by MTT assays and icariside II could enhance cellular GSH levels by ELISA assay. Then, the potential roles of ERK, Akt and JNK in the regulation of icariside II-induced Nrf2-dependent ARE transcriptional activity as well as ARE-mediated endogenous HO-1 and glutathione GST protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Since EGCG was able to inhibit the activation of NF-κB signal pathway ( Figure 6I), its down-regulation on the expression of cytokines, especially for IL-6, IL-10, TGF-β and GM-CSF was further validated in MDSCs accordingly ( Figure 6J-M). In addition, nuclear factor erythroid 2-related factor 2 (Nrf2) and Nrf2-related antioxidant protein OH-1 play a crucial role in defensing cellular stress [33], and endogenous antioxidant enzymes, such as catalase (CAT), superoxide dismutase (SOD) and glutathione-S-transferase (GST) [34]. However, no significant differences in these genes in EGCG treatment groups were observed when compared to the control group ( Figure S2).…”
Section: Egcg Targets Mdscs Through the Canonical Pathwaysmentioning
confidence: 99%
“…Since EGCG was able to inhibit the activation of NF-κB signal pathway ( Figure 6I), its down-regulation on the expression of cytokines, especially for IL-6, IL-10, TGF-β and GM-CSF was further validated in MDSCs accordingly ( Figure 6J-M). In addition, nuclear factor erythroid 2-related factor 2 (Nrf2) and Nrf2-related antioxidant protein OH-1 play a crucial role in defensing cellular stress [33], and endogenous antioxidant enzymes, such as catalase (CAT), superoxide dismutase (SOD) and glutathione-S-transferase (GST) [34]. However, no significant differences in these genes in EGCG treatment groups were observed when compared to the control group ( Figure S2).…”
Section: Egcg Targets Mdscs Through the Canonical Pathwaysmentioning
confidence: 99%
“…Antioxidant response element (ARE) is a cis-acting sequence located in promoter regions of genes encoding phase II enzymes. The activation of gene transcription via the ARE is regulated by nuclear factor-erythroid 2-related factor (Nrf2) signaling [7]. In an inactive state, Nrf2 is retained in the cytoplasm by binding to Kelch-like ECH-associated protein (Keap1).…”
Section: Basic Researchmentioning
confidence: 99%
“…A number of studies have found that overexpression of antioxidant enzyme occurs in cancer resistance to radiation therapy, whereas blocking these antioxidant defenses can enhance radiation sensitivity [59]. Nuclear factor-erythroid 2-related factor-2 (Nrf2), a redox sensitive transcription factor, regulates the expression of several detoxifying enzymes, such as heme oxygenase-1 (HO-1), and nicotinamide adenine dinucleotide phosphate (reduced) (NADPH): quinone oxidoreductase-1 (NQO-1), through binding to antioxidant response element (ARE) within gene promoters [9, 10]. Ionizing radiation (IR) causes DNA nucleotide modifications, single and double strand DNA breaks (SSBs and DSBs), both directly and indirectly via formation of free radicals and ROS.…”
Section: Introductionmentioning
confidence: 99%